National surveys of military personnel, nursing students, and the public: drivers of military nursing careers. - Donelan, Karen; Romano, Carol; Desroches, Catherine; Applebaum, Sandra; Ward, Johanna Rm; Schoneboom, Bruce A; Hinshaw, Ada Sue; Buerhaus, Peter (Military Medicine, 2014)
Objectives: The U.S. health care system is facing a projected nursing shortage of unprecedented magnitude. Although military nursing services recently have been able to meet their nursing recruitment quotas, national studies have predicted a long-term nursing shortage that may affect future recruitment for the Nurse Corps of the three military services. Data are needed to plan for recruitment incentives and the impact of those incentives on targeted populations of likely future nurses.Methods: Data are drawn from three online surveys conducted in 2011-2012, including surveys of 1,302 Army, Navy, and Air Force personnel serving on major military bases, 914 nursing students at colleges with entry Bachelor of Science in Nursing programs located nearby major military bases, and a qualitative survey of 1,200 young adults, age 18-39, in the general public.Findings: The three populations are different in several demographic characteristics. We explored perceptions of military careers, nursing careers and barriers, and incentives to pursue military nursing careers in all populations. Perceptions differ among the groups.Conclusion: The results of this study may help to inform strategies for reaching out to specific populations with targeted messages that focus on barriers and facilitators relevant to each to successfully recruit a diverse Nurse Corps for the future.